LIMITS OF PARTICIPATION OF PARENTS AND OTHER PERSONS IN THE PROCESS OF RECEIVING MEDICAL CARE AND SERVICE FOR A CHILD - Mkrtumyan, Anna (State and Law, 2025)
Children are rights holders with a progressively evolving ability to make their own decisions. They have the right to express their views on all matters that affect them, namely in the field of health care, and to have their view properly taken into account. Children who actively participate in individual decision-making processes concerning them are likely to be more informed, to feel better prepared, to experience less anxiety about the unknown and to feel a sense of control, resulting in increased cooperation, better adjustment and adherence to treatment. In this context, parents (legal representatives) and healthcare professionals involved need to understand the importance of their role in supporting children in this process. Parents (legal representatives) should support and guide children to understand the need to seek medical care and services and to intervene in the process in accordance with the child’s age, maturity and evolving capabilities. The role of medical workers in this matter is more comprehensive, because they are obliged to ensure the awareness of parents (legal representatives) and children in this matter and to contribute to its implementation. Other persons may be involved in the process of receiving medical care the child with the direct knowledge and consent of the parents (legal representatives) and the medical professional.